Pengembangan Model Pembelajaran Asuhan Kehamilan Terintegrasi Pada Pendidikan Kebidanan - Pranbandari, Fitria (Universitas Harapan Bangsa Purwokerto, 2019)
Abstract The midwifery care learning model that is currently underway does not answer the needs of women. Implementation of education by emphasizing learning that separates the presentation between one subject and other subjects will cause quite serious problems, especially for midwifery students who are expected to become professional midwives who are expected to play an active role in reducing the MMR and IMR. Competence is an underlying characteristic of a person related to the effectiveness of individual performance in his work or basic characteristics of individuals who have a causal relationship or as a cause and effect with criteria that are used as a reference, effective or excellent or superior performance at work or in certain situations, so that learning models are needed integrated ie a teaching or instructional model to help students develop in-depth and indirect understanding of a systematic set of knowledge simultaneously and practice critical thinking, involving several required subjects or disciplines so that boundaries between subjects can be abolished to provide a learning experience that is meaningful. One of the courses is pregnancy care integrated with aspects of women's needs, professional ethics, communication, religion, culture, and psychology to improve student competency in pregnancy care. Keywords: integrated learning model, pregnancy care.